1996
DOI: 10.1002/(sici)1097-4644(19960401)61:1<18::aid-jcb3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-derived soluble factors block osteoblast differentiation in culture

Abstract: Bone metastasis is a common event and a major cause of morbidity in prostate cancer patients. After colonization of bone, prostate cells induce an osteoblastic reaction which is not associated with marrow fibrosis (i.e., osteoblast but not fibroblast proliferation). In the present study we test the hypothesis that the tumoral prostatic cell line (PC-3) secretes factors that block the osteoblast differentiation process, resulting in an increase of the relative size of the proliferative cell pool. Our results, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…As expected, the SaOs2 cells had high levels of ALP activity which declined when co-cultured either directly or indirectly with PC3 or LNCaP cells suggesting that secreted factors from the prostate cancer cells inhibit osteoblast activity. Similarly, previous studies demonstrated that mouse osteoblasts or rat fetal calvaria co-cultured with PC3 cells exhibited a decrease in both ALP activity and the mineralization process, suggesting that PC3 cells secrete molecules that inhibit osteoblast differentiation [35,41], thus supporting the more osteolytic phenotype observed in bone metastasis induced by PC3 cells [27,35,37].…”
Section: Discussionsupporting
confidence: 55%
“…As expected, the SaOs2 cells had high levels of ALP activity which declined when co-cultured either directly or indirectly with PC3 or LNCaP cells suggesting that secreted factors from the prostate cancer cells inhibit osteoblast activity. Similarly, previous studies demonstrated that mouse osteoblasts or rat fetal calvaria co-cultured with PC3 cells exhibited a decrease in both ALP activity and the mineralization process, suggesting that PC3 cells secrete molecules that inhibit osteoblast differentiation [35,41], thus supporting the more osteolytic phenotype observed in bone metastasis induced by PC3 cells [27,35,37].…”
Section: Discussionsupporting
confidence: 55%
“…Despite the prevalence of prostate cancer metastasis to the skeleton, the molecular mechanisms of bone tropism are poorly understood. Previous studies suggest that prostate cancer cell adhesion, extravasation, migration, and interaction with bone cells are critical determinants that govern prostate cancer bone colonization (2)(3)(4). Reports using clinical prostate cancer metastasis specimens (5-7) and experimental cell and animal models (8)(9)(10) found the bone-specific proteins osteocalcin and bone sialoprotein to be expressed in a heterogeneous manner by human prostate cancer specimens.…”
Section: Introductionmentioning
confidence: 99%
“…An explanation could be that PC3 cells produce parathyroid hormone‐related peptide (PTHrP) and transforming growth factor α (TGF‐α), both stimulators of the osteolytic response (12, 13) . However, it has been shown that PC3 cells secrete a factor or factors that stimulates the mitogenic activity of osteoblast‐like cells (14–16) . The PC3 derived mitogens were found to be proteins with molecular weights ranging from 20 to 30 kDa (14, 15) .…”
Section: Introductionmentioning
confidence: 99%